Universality and cultural variation in the conceptualisation of love via metaphors, metonymies and cultural scripts: The case of Montenegrin - Perović, Slavica; Vuković-Stamatović, Milica (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This paper studies the conceptualisation of love by the Montenegrin student population, via conceptual metaphors, metonymies and related concepts, as well as through the lenses of cultural scripts. The corpus with the conceptual instantiations was collected using a sentence-completion elicitation questionnaire, which was administered to Montenegrin university students. The aim was to identify the cognitive model of love of the targeted population, and to determine the level of universality and cultural variation of the conceptualisations identified. The results suggest that the level of universality and culture-specificity depends on how generally we define the conceptualisation – the superordinate-level, i.e. more general and abstract metaphors displayed more universality, whereas more cultural specificity was likely to be found in the basic-level metaphors, i.e. narrower metaphors.